Las mujeres zapotecas del istmo de Tehuantepec – México en el siglo XIX - Leticia Reina (Nuevo mundo - Mundos Nuevos, 2015)
The presence of zapotec women, their elegance-finesse and importance in the region’s economical and cultural development, constituted an exceptional case among the women from other Mexican ethnic groups. This article analyzes the origins and elements that were at stake to mold and define the predominant roll of the zapotec women to underpin some elements that made the zapotecs, the dominant ethnic group of the Mexican isthmus region. This article’s object consists on explaining women’s economic and social roll when facing the death or absence of husbands or adult men in general, these were substituted by foreigners who were socially, economically and culturally integrated in the late Nineteenth century. Nevertheless, they obtained "benefits" from the modernizing project, especially in the late nineteenth century when the Tehuantepec railroad was built and the Mexican State was consolidated. Additionally, we will try to explain how on account of this situation the group was enriched and although a strong internal stratification was generated, they elaborated a majestic culture in which women played a very important role as "head of household" and carriers of social capital as they would reproduce culture of prestige.